Heritable variation of mRNA decay rates in yeast - Andrie, Jennifer M. (Genome Res, 2014)
Gene expression levels are determined by the balance between rates of mRNA transcription and decay, and genetic variation in either of these processes can result in heritable differences in transcript abundance. Although the genetics of gene expression has been a subject of intense interest, the contribution of heritable variation in mRNA decay rates to gene expression variation has received far less attention. To this end, we developed a novel statistical framework and measured allele-specific differences in mRNA decay rates in a diploid yeast hybrid created by mating two genetically diverse parental strains. We estimate that 31% of genes exhibit allelic differences in mRNA decay rates, of which 350 can be identified at a false discovery rate of 10%. Genes with significant allele-specific differences in mRNA decay rates have higher levels of polymorphism compared to other genes, with all gene regions contributing to allelic differences in mRNA decay rates. Strikingly, we find widespread evidence for compensatory evolution, such that variants influencing transcriptional initiation and decay have opposite effects, suggesting that steady-state gene expression levels are subject to pervasive stabilizing selection. Our results demonstrate that heritable differences in mRNA decay rates are widespread and are an important target for natural selection to maintain or fine-tune steady-state gene expression levels.